PREVENTION OF DISEASES OF THE UPPER JAW - Olimbayev Bekzodjon Muzaffar o‘g‘li (Web of Journals Publishing, 2026)
The article discusses preventive strategies for maxillary diseases including inflammatory, traumatic, degenerative, and neoplastic conditions. The importance of oral hygiene, elimination of infection foci, and comprehensive preventive programs is emphasized. Based on clinical observations and literature analysis, a preventive framework is proposed.
Keywords: Maxilla, prevention, sinusitis, osteomyelitis, periodontal disease, oral hygiene